1999
DOI: 10.1038/sj.bjp.0702572
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of 5‐HT1B and 5‐HT1D receptors in the sumatriptan‐induced constriction of porcine carotid arteriovenous anastomoses

Abstract: 1 It has previously been shown that the antimigraine drug sumatriptan constricts porcine carotid arteriovenous anastomoses via 5-HT 1 -like receptors, identical to 5-HT 1B/1D receptors. The recent availability of silent antagonists selective for the 5-HT 1B (SB224289) and 5-HT 1D (BRL15572) receptor led us to further analyse the nature of receptors involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…The vasoconstrictor effect increases the resistance of carotid arteries and reduces cerebral blood flow (CBF) (Feniuk et al, 1989;den Boer et al, 1991;De Vries et al, 1999b). Cerebral vessels are assumed to dilate during migraine headache and CBF changes during migraine attacks, as reported by Olesen et al (1990).…”
Section: Introductionmentioning
confidence: 96%
“…The vasoconstrictor effect increases the resistance of carotid arteries and reduces cerebral blood flow (CBF) (Feniuk et al, 1989;den Boer et al, 1991;De Vries et al, 1999b). Cerebral vessels are assumed to dilate during migraine headache and CBF changes during migraine attacks, as reported by Olesen et al (1990).…”
Section: Introductionmentioning
confidence: 96%
“…The pigs had been used in in vivo experiments studying the effects of ␣-adrenoceptor and serotonin receptor agonists and antagonists under pentobarbital (600 mg IV) anesthesia. 15 The ethics committee of Erasmus University Rotterdam dealing with the use of animals for scientific experiments approved the protocol for this investigation. Hearts were explanted at the end of the experiment, and the coronary arteries were removed immediately and handled in the same way as HCAs.…”
Section: Tissue Collectionmentioning
confidence: 99%
“…SB224289, but not BRL15572 antagonises the effects of sumatriptan (Fig. 2) [12]. Despite the fact that our recent investigation revealed that BRL15572, has a low affinity for the porcine 5-HT 1D receptor in contrast to the human 5-HT 1D receptor [13], it is obvious that the 5-HT 1B receptor mediates carotid vasoconstrictor response.…”
mentioning
confidence: 81%